2021
DOI: 10.1053/j.seminoncol.2021.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mortality of cancer patients with COVID-19 in a Brazilian cancer center

Abstract: Introduction To analyze COVID-19 mortality in cancer patients and associated factors such as age, sex, type of insurance, situation at COVID-19 diagnosis, and cancer histology during the pandemic at a cancer center in Brazil. Methods Cross-sectional study carried out from April 02, 2020 to August 31, 2020 at A.C. Camargo Cancer Center (ACCCC), in São Paulo, Brazil. Cases were extracted from the Hospital Cancer Registry. COVID-19 lethality rates by histology were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…28 In a Brazilian study, patients with lung or hematological cancer and patients under oncological treatment had a higher risk of death among patients with COVID-19. 14 Mortality due to COVID-19 in patients with cancer could be heterogeneous for different kinds of primary tumors, and individualized strategies for preventing or reducing the risk of mortality in COVID-19 patients with cancer are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 In a Brazilian study, patients with lung or hematological cancer and patients under oncological treatment had a higher risk of death among patients with COVID-19. 14 Mortality due to COVID-19 in patients with cancer could be heterogeneous for different kinds of primary tumors, and individualized strategies for preventing or reducing the risk of mortality in COVID-19 patients with cancer are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…8 They are often older, immunosuppressed, and poorly nourished and have different comorbidities and adverse effects caused by oncological treatment. 5,7,8,14 Hematological malignancies, associated with greater susceptibility due to immune system impairment, have been associated with a poor prognosis for COVID-19 patients with cancer. 8,14,28 Oncological treatments have also been related to the risk of mortality due to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and pooled analysis of over 18,650 cancer patients with COVID-19 from 52 international studies reported a 25.6% mortality rate [14•]. Other individual and pooled studies report mortality rates between 12 and 30% and suggest that a cancer diagnosis is associated with worse COVID-19 outcomes [15][16][17][18][19][20][21]. In contrast, some studies report more comparable outcomes between cancer and non-cancer patients [22,23].…”
Section: Covid-19 and Risks In Cancer Patientsmentioning
confidence: 99%
“…Other centers have also reported low rates of COVID-19 infection while on systemic therapy [24]. In contrast, some studies suggest that mortality is higher in patients having received active cancer treatment [17,25,26]. A large case-control study including over 73 million electronic medical records reported patients with cancer had significantly higher risks of COVID-19 infection and worse outcomes [21].…”
Section: Covid-19 and Risks In Cancer Patientsmentioning
confidence: 99%